2020
DOI: 10.1186/s13613-020-00665-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary [TIMP-2] × [IGFBP7] and serum procalcitonin to predict and assess the risk for short-term outcomes in septic and non-septic critically ill patients

Abstract: Background: Biomarkers can play a critical role by facilitating diagnosis and stratification of disease, as well as assessment or prediction of disease severity. Urinary tissue inhibitor of metalloproteinase-2 and insulin-like growth factor binding protein 7 product ([TIMP-2] × [IGFBP7]) predict the development and progression of AKI and recently procalcitonin (PCT), a widely used biomarker for sepsis diagnosis and management, has been associated with AKI occurrence in ICU patients. To assess combinations of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Pooled results for 23 studies including more than 150,000 non-ICU patients illustrate that quick SOFA has poor sensitivity for sepsis mortality (51%) and organ failure (47%) ( 15 ). Numerous studies have shown that urinary (TIMP-2) × (IGFBP7) is sensitive and specific for AKI including for patients with sepsis ( 5 , 16 18 ). Many patients with infection are admitted to hospital, and, in the absence of shock or respiratory failure, few are admitted to ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled results for 23 studies including more than 150,000 non-ICU patients illustrate that quick SOFA has poor sensitivity for sepsis mortality (51%) and organ failure (47%) ( 15 ). Numerous studies have shown that urinary (TIMP-2) × (IGFBP7) is sensitive and specific for AKI including for patients with sepsis ( 5 , 16 18 ). Many patients with infection are admitted to hospital, and, in the absence of shock or respiratory failure, few are admitted to ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays a significant role in the occurrence and development of AKI [ 8 , 9 , 10 ]. Many well-known inflammatory markers, including neutrophils [ 11 ], platelets [ 12 , 13 ] and procalcitonin [ 14 ] have been shown to be related to AKI. However, focusing on just one indicator is of limited use, as these biomarkers are always affected by other confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of using filtration markers, such as creatinine, to diagnose and assess recovery from acute and subacute kidney damage are well recognized. Although preliminary work assessing the utility of biomarkers to predict AKD is underway, these alternative measures of kidney function require further validation in this setting prior to clinical use [11, 15].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Despite this, AKD has not been systematically studied, and its relationship with long-term clinical outcomes is poorly understood. Data from previous studies have been variably limited by short follow-up time [7, 8], non-consensus definitions of exposure [7-11], clinically enriched populations [10, 12-16], lack of adjustment for confounders [7, 9, 12, 14-16], and pooling of heterogeneous data from community and hospital settings [17]. The only published study to examine AKD without AKI included patients with unknown baseline kidney function [17].…”
Section: Introductionmentioning
confidence: 99%